KOMUNIKASI INTERPERSONAL DIADIK ANTARA ANAK DAN ORANG TUA TIRI DALAM KELUARGA - Intan Hamidah Yuzakky Saputri; Sukarelawati Sukarelawati; Ali Alamsyah Kusumadinata (JURNAL KOMUNIKATIO, 2022)
Communication between children and stepparents in the family is dyadic interpersonal communication. Dyadic communication is a type of communication that involves the relationship of two people. Dyadic interpersonal communication will be effective if the communication builds a shared understanding based on an attitude of openness, empathy, a supportive attitude or a positive attitude, and equality. This study examined dyadic interpersonal communication between children and stepparents in the family. The author used a qualitative descriptive method. The researchers collected primary data from interviews with five children who have stepparents. The study found the four elements of interpersonal communication in dyadic communication between children and stepparents. The element of openness was the most crucial factor in dyadic interpersonal communication between children and stepparents because it was the beginning of the presence of other aspects of effective communication. In addition, open communication can build positive, equal, and empathetic relationships.